The Origin of Open-Angle Glaucoma and Modern Clinical Diagnostic Methods! - Rustamovna, Abdullaeva Dilorom (American Journal of Bioscience and Clinical Integrity, 2025)
Glaucoma is a leading cause of blindness worldwide, characterized by progressive damage to the optic nerve and irreversible loss of retinal neurons. The disease poses significant challenges in both diagnosis and treatment, as its symptoms often remain unnoticed until the later stages. Early detection is crucial for preventing severe vision impairment, yet the asymptomatic nature of glaucoma makes timely diagnosis difficult. While lost neurons cannot be regenerated, appropriate therapeutic interventions can effectively slow disease progression, preserving visual function. This study explores current diagnostic techniques and treatment strategies for glaucoma, emphasizing the importance of early intervention and long-term management in mitigating its impact on vision loss.